Land acquisition induced conflicts in suburban China: a procedural perspective. (11th May 2019) - Wang, Mark Y.L.; Song, Yanan; Li, Chen
Abstract: Protests and opposition to land acquisition from displaced peasants for fair compensation occur on a daily basis in China and have become the most prominent social problem in rural parts of the country. Employing a procedural perspective on conflict, this paper aims to uncover the complexities and tensions that are triggered in the process by drawing on a case of a land confiscation in Jining City, a medium‐size city in Shandong Province, China. Our research shows that conflicts exist at various scales: both between the local governments and rural households and between the village officials and villagers. The paper argues that ambiguity in de jure and de facto land acquisition procedures has resulted in both an escalation of conflict and increasing inequality in the outcomes and benefits of the process. We discuss and conclude that the differences between de jure and de facto procedures in the process of land acquisition are a significant institutional barrier in the resolution of conflict in this important issue for rural China.